MARKETING MIX ANALYSIS OF NATURAL TOURISM AREA 'KAWAH PUTIH’ AND ITS EFFECT ON VISITORS’ DECISION - Isyana Rahayu; Dodik Ridho Nurrochmat; Achmad Fachrodji (Indonesian Journal of Business and Entrepreneurship (IJBE), 2015)
Kawah Putih is one of the leading tourist places in Bandung which has significantly contributed to the revenue of travel business division in the Forestry Housing as the manager. The revenue obtained depends on the marketing mix strategy conducted by the management because the marketing mix is the elements which become a consideration basis when making marketing communication strategy services in order to understand the demands of tourists. Therefore, the objectives of this study were to obtain and understand information and analyze the visitors’ responses on the natural tourism area related to the marketing mix that has been implemented by the management. The dependent variables included the elements of marketing mix, that involves 7P – product, price, place, promotion, people, procees and physical evidence, while the independent variable included the visitors’ decision. From the validity and tests, it is revealed that the overall regression model bring effects or at least there is one variable of the marketing mix factors that influences the decision of the visitors. From the data analysis, it is found that the process variables and physical appearance do not significantly affect the decision of the visitors. The other variables. that involve variables of product, price, place, promotion, and human have significantly influence the visitors’ decision.Keywords: Marketing mix, Kawah Putih, decision of visitors, touristsABSTRAKKawah Putih merupakan salah satu wisata unggulan Kota Bandung dan telah berkontribusi cukup signifikan untuk pendapatan divisi bisnis wisata Perum Perhutani. Pendapatan yang diperoleh tergantung dari strategi bauran pemasaran yang dilakukan oleh pengelola karena pada bauran pemasaran terdapat unsur atau elemen yang menjadi dasar pertimbangan pembuatan strategi komunikasi pemasaran jasa dalam rangka untuk memahami tuntutan dari wisatawan. Tujuan penelitian ini adalah memperoleh informasi, memahami dan menganalisis tanggapan pengunjung kawasan wisata alam tentang bauran pemasaran yang telah dilakukan oleh pihak pengelola. Variabel independennya adalah elemen bauran pemasaran 7P yaitu product, price, place, promotion, people, procees dan physical evidence, sedangkan untuk variabel dependennya adalah keputusan pengunjung. Pada uji validitas dan reabilitas diketahui data hasil penelitian bisa digunakan. Pada uji asumsi didapatkan bahwa data memenuhi asumsi normal serta tidak terdapat multikolinearitas dan heteroskedasititas Dari hasil analisis data dapat diketahui variabel proses dan penampilan fisik tidak berpengaruh terhadap keputusan pengunjung. Sedangkan untuk variabel lainnya yang mencakup variabel produk, harga, tempat, promosi, dan manusia signifikan berpengaruh terhadap respon keputusan pengunjung.Kata kunci: marketing mix, Kawah Putih, keputusan pengunjung, wisatawan